The Influence of the PBL (Problem Based Learning) Model assisted by the Snakes and Ladders Game on the Critical Thinking Skills of Fifth Grade Civics Students at SDN Inpres Kambilo - Hasrini, Hasrini; Ihsan, Ihsan; Jannah, Miftahul (Journal of Educational Sciences, 2025)
This study aims to analyze the effect of applying the Problem Based Learning (PBL) model assisted by snakes and ladders game on improving students' critical thinking skills in Civic Education (Civics) subjects at SDN Inpres Kambilo. Critical thinking skills are one of the important competencies that students must have to face the challenges of the 21st century. However, initial observations show that students' critical thinking skills at SDN Inpres Kambilo still need to be improved. The PBL approach was chosen because it encourages students to actively solve real problems, while the snakes and ladders game was integrated to increase motivation and learning interaction. The research sample consisted of two groups, namely the experimental group taught with the PBL model assisted by snakes and ladders and the control group taught with conventional methods. Data on critical thinking skills were collected through a validated description test and analyzed using t-test. The results of the study before learning using snakes and ladders media, the average score obtained was 60 and after using snakes and ladders media, the average score was 80. Semplel t test results obtained a significance value of 0.000 (p <0.05), it can be concluded that there is a significant difference in the application of snakes and ladders media.